EAGER: efficient ancient genome reconstruction. Issue 1 (December 2016) - Peltzer, Alexander; Jäger, Günter; Herbig, Alexander; Seitz, Alexander; Kniep, Christian; Krause, Johannes; Nieselt, Kay
Abstract Background The automated reconstruction of genome sequences in ancient genome analysis is a multifaceted process. Results Here we introduce EAGER, a time-efficient pipeline, which greatly simplifies the analysis of large-scale genomic data sets. EAGER provides features to preprocess, map, authenticate, and assess the quality of ancient DNA samples. Additionally, EAGER comprises tools to genotype samples to discover, filter, and analyze variants. Conclusions EAGER encompasses both state-of-the-art tools for each step as well as new complementary tools tailored for ancient DNA data within a single integrated solution in an easily accessible format.